Protocol to develop A 3D tumor model for drug testing applications - Prasiddha Guragain; Sunil Singh; Hossein Tavana (SLAS Discovery)
Three-dimensional (3D) tumor models provide physiologically relevant tumor environments and have become a major tool in cancer research and drug discovery. This article presents a protocol for creating a 3D organotypic tumor model by embedding a cancer cell spheroid within a collagen matrix containing dispersed fibroblasts. This model offers significant advantages over the conventional monolayer cell culture, monoculture spheroids of cancer cells, and intermixed co-culture of cancer and stromal cells by mimicking the spatial organization and mechanical properties of a solid tumor. Compatible with robotic automation, our protocol significantly enhances reproducibility and scalability of creating a tumor model to study tumor-stromal interactions and test therapeutic compounds